Preservice teachers' in‐the‐moment teaching decisions in reading. (31st August 2016) - Griffith, Robin
Abstract: This study examines the types of in‐the‐moment teaching decisions 97 preservice teachers made while teaching reading and how their growing bodies of teacher knowledge influenced their abilities to think, know, feel and act like a teacher (Feiman‐Nemser, 2008 ). Findings indicated that the teacher educator's use of "metacognitive decision‐making" to promote a culture of identifying, drawing attention to, reflecting on and evaluating teaching decisions influenced the preservice teachers' abilities to think, know, feel and act like a teacher. These findings have implications for teacher education and for those who support novice teachers.